Discovery of ASP5878: Synthesis and structure–activity relationships of pyrimidine derivatives as pan-FGFRs inhibitors with improved metabolic stability and suppressed hERG channel inhibitory activity. (1st April 2022) - Kuriwaki, Ikumi; Kameda, Minoru; Iikubo, Kazuhiko; Hisamichi, Hiroyuki; Kawamoto, Yuichiro; Kikuchi, Shigetoshi; Moritomo, Hiroyuki; Terasaka, Tadashi; Iwai, Yoshinori; Noda, Atsushi; Tomiyama, Hiroshi; Kikuchi, Aya; et al.
Graphical abstract: Abstract: Fibroblast growth factor receptor 3 (FGFR3) is an attractive therapeutic target for the treatment of bladder cancer patients harboring genetic alterations in FGFR3. We identified pyrimidine derivative ASP5878 (27 ) with improved metabolic stability and suppressed human ether-á-go-go related gene ( h ERG) channel inhibitory activity by the optimization of lead compound 1 . Based on prediction of the metabolites of 1, an ether linker was introduced in place of the ethylene linker to improve metabolic stability. Moreover, conversion of the phenyl moiety into the pyrazole ring resulted in the suppression of h ERG channel inhibitory activity, possibly due to the weaker π-π stacking interaction with Phe656 in the h ERG channel by a reduction in π-electrical density of the aromatic ring. ASP5878 showed potent in vitro FGFR3 enzyme and cell growth inhibitory activity, and in vivo FGFR3 autophosphorylation inhibitory activity. Moreover, ASP5878 did not affect the h ERG current up to 10 µM by in vitro patch-clamp assay, and a single oral dose of ASP5878 at 1, 10, and 100 mg/kg did not induce serious adverse effects on the central nervous, cardiovascular, and respiratory systems in dogs. Furthermore, ASP5878 exhibited lower total clearance than hepatic blood flow and high oral bioavailability in rats and dogs, and moderate brain penetration in rats.